Discovery of broadly neutralizing VHHs against short-chain α-neurotoxins using a consensus toxin as an antigen - Anna Damsbo; Melisa Benard-Valle; Tom Jansen; Nick J. Burlet; Max D. Overath; Alid Guadarrama-Martínez; Kim Boddum; Alejandro Alagon; Esperanza Rivera-de-Torre; Andreas H. Laustsen (mAbs)
Snakebite envenoming is a neglected tropical disease that afflicts millions of people globally, leading to substantial morbidity and mortality. Developing novel antivenoms, particularly recombinant antivenoms based on broadly neutralizing monoclonal antibodies, offers a promising strategy to address the challenge posed by venom variability. However, the extensive diversity of snake venom toxins across species and geographical regions makes this goal inherently complex. Consequently, there is a pressing need for robust discovery methodologies capable of identifying broadly neutralizing antibodies with high affinity and functional potency against a wide range of toxin families. In this study, we engineered a short-chain consensus (SCC) α-neurotoxin to serve as an antigen for a phage display – based antibody discovery campaign. The SCC was expressed using a yeast system, enabling the identification of seven variable domains of heavy-chain-only antibodies (VHHs) from immune libraries. These VHHs exhibited nanomolar-binding affinities and low dissociation rates across a panel of short-chain α-neurotoxins, which translated into in vitro neutralization, protecting the target receptor. The best two VHHs also conferred protection against lethality in a rodent model. These results highlight the unexpected value of consensus toxins in antibody discovery and offer a viable route for developing recombinant antivenoms with broad-spectrum efficacy.